Strength and stiffness of timber joints with very high strength steel dowels. (15th January 2017) - Sandhaas, Carmen; van de Kuilen, Jan-Willem G.
Highlights: Tests with different wood species, dowel diameters and steel grades have been done. Dowel-type fasteners with maximum strength of up to 1300 MPa have been applied. Load bearing capacity is increased when replacing ordinary with high strength dowels. The European Yield Model can be applied on the tested steel grades and species. The load bearing capacity showed no correlation with wood density on species level. The prediction of Eurocode 5 overestimates the stiffness of multiple dowelled joints Abstract: Tests on double-shear timber-to-timber joints and double-shear timber joints with slotted-in steel plates loaded parallel-to-grain were undertaken. The used species were spruce, beech, cumaru and azobé (ekki) with one, three and five dowels in a row. Two different steel qualities were used, high strength steel (hss) and very high strength steel (vhss) dowels. The experimental results have shown that the load carrying capacity of joints with vhss dowels is higher than for joints using hss dowels whilst still providing enough plastic deformation capacity to allow for ductile failure modes. No correlation between load carrying capacity and density within one wood species could be observed. The observed effective number of fasteners is lower for the joints with vhss dowels and depends also on the used wood species and the slenderness of dowels. Also for the stiffness Kser, an effective number of fasteners for the joints with more than one dowel in a row could be observed. The well-established Johansen model can be used to design these types of joints.